The Role of Sex, Ethnicity, Age, and Nutritional Status in the Seropositivity of the Measles Vaccine - Nurlatifah, H. R. Teni; Barlianto, Wisnu; Wiyasa, I Wayan Arsana; Kusuma, H. M. S. Chandra; Sari, Tita Luthfia; Bachtiar, Novilia Sjafri (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study investigates the relationship between sex, ethnicity, age, nutritional status with the seropositivity of the Edmonston-Zagreb vaccine in children. METHODS: A cross sectional, observational study was conducted. A total of 45 children were differentiated based on sex, ethnicity, age, and nutritional status when they received the Edmonston-Zagreb measle vaccine for the first time. Flow cytometry was used to look at differences in antibody status as well as populations of CD-4 and CD-8 cells that release IFN- γ. RESULTS: We found no significant differences in antibody levels or CD-4 and CD-8 cell populations that secrete IFN- γ between boys and girls (p > 0.05). Besides, similar results were also confirmed in comparisons between Javanese and Sundanese ethnic groups, 9 months versus more than 9 months of age, or normal versus low body mass index (p > 0.05). CONCLUSIONS: We conclude that sex, race, age, and nutritional status had no effect on immune response to vaccination. As a result, there was no barrier to seroconversion and optimal immunological performance in the children in this trial who received the Edmonston-Zagreb measles vaccination.